Pengaruh Capital Intensity, Thin Capitalization, dan Konservatisme Akuntansi terhadap Penghindaran Pajak - safira Dafa Amelia; Aisyaturrahmi Aisyaturrahmi (Universitas Katolik Soegijapranata, Semarang, 2026)
This study aims to analyze the effect of capital intensity, thin capitalization, and accounting conservatism on tax avoidance in companies. The background of this research is based on Indonesia’s relatively low tax ratio compared to other ASEAN countries, which indicates the presence of tax avoidance practices among corporate taxpayers. This study employs a quantitative approach using secondary data obtained from companies’ financial statements. The sampling technique used is purposive sampling, while data analysis is conducted using multiple linear regression. The results show that capital intensity and thin capitalization have a significant effect on tax avoidance, while accounting conservatism has a varying influence depending on the company’s condition. These findings indicate that asset structure and corporate financing policies can encourage tax avoidance practices. Therefore, stricter supervision and appropriate policies are needed to minimize such practices.